2014
DOI: 10.1021/jp509046n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of a Model Hydrocarbon Mixture Over HY Zeolite Under Dry and Wet Conditions

Abstract: International audienceAdsorption behavior of a hydrocarbon mixture (propene, toluene, decane) mimicking Diesel cold-start was investigated under dry and wet conditions for commercial HY zeolites with a Si/Al ratio ranging from 2.5 to 100. Textural and structural characterizations were carried out using N-2 adsorption at 77 K and X-ray diffraction. In situ FTIR spectroscopy of adsorbed pyridine was exploited to probe acidic sites. The methodology used in this study consisted of adsorption phase at 35 degrees C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 38 publications
4
26
0
Order By: Relevance
“…The XPS results (see Figure 2) show that the addition of Fe, and especially La, resulted in lowering of the Pd oxidation state. As the oxygen in the zeolite framework is mostly associated with Lewis acid sites [10][11][12][18][19][20]. The lower oxidation state of the Pd might indicate a lower number of Lewis acid sites, which could be an explanation for the lower desorption quantities observed in the toluene-TPD in Figure 8.…”
Section: Beamentioning
confidence: 95%
See 3 more Smart Citations
“…The XPS results (see Figure 2) show that the addition of Fe, and especially La, resulted in lowering of the Pd oxidation state. As the oxygen in the zeolite framework is mostly associated with Lewis acid sites [10][11][12][18][19][20]. The lower oxidation state of the Pd might indicate a lower number of Lewis acid sites, which could be an explanation for the lower desorption quantities observed in the toluene-TPD in Figure 8.…”
Section: Beamentioning
confidence: 95%
“…These results contradict the results from the propene-TPD experiments, where the addition of Pd resulted in lower storage capacity of propene in dry conditions. We suggest that the reason for this difference is that the phenyl ring of toluene can also adsorb Lewis acid sites [10][11][12][18][19][20], such as Pd, while propene preferentially interacts with Brønsted acid sites through hydrogen bonding with the π electrons in the C=C bond [17]. Some desorption peaks also appear at higher temperatures in Figure 5.…”
Section: Beamentioning
confidence: 96%
See 2 more Smart Citations
“…This will slow down the diffusion of CH 3 I. In our previous works dealing about multiple-hydrocarbon adsorption by different zeolitic structures, we have shown that adsorbed amounts and breakthrough profiles were not only influenced by the chemical nature of the adsorbates but also by the pore connectivity and topology [17,40,41]. Finally, the presence of sodium in fauajsite zeolites appears also to adversely affect the filtering efficiency by inducing a change in the distribution or speciation of silver species (as stated in the characterization part).…”
Section: B) Adsorption Capacities At Breakthrough and Diffusional Conmentioning
confidence: 99%